Kepemimpinan Perempuan dalam Meningkatkan Mutu Pendidikan - Sitti Zulqaidah; Zulkifli Mustang; Syamsuddin (Yayasan Ishlahul Muslimin Konawe Selatan, 2025)
This article aims to examine and analyze Women's Leadership in Improving the Quality of Education at MTs Asy-Syafi'iyah Baruga Kendari. This research use desciptive qualitative approach.Data collection techniques were carried out through interviews, observation and documentation. Data analysis through the process of data reduction, data presentation and drawing conclusions as well as data validity techniques through data triangulation (technique, source and time), extension of observations, and conducting Member checks. The results showed that: 1) The principal's method of building effective communication between employees at MTs Asy-syafi'iyah Baruga Kendari, namely by persuasive methods. 2) The method of the Head of MTs Asy-Syafi'iyah Baruga Kendari in making decisions is through deliberation by consensus by holding joint meetings and decisions are decided based on the majority of votes. 3) Women's Leadership in improving the Quality of Education at MTs Asy-syafi'iyah Baruga Kendari, namely by planning what will be planned in the aspects., then dividing personnel and tasks according to their respective fields. After that, monitoring and evaluation of the level of achievement was carried out.